2012
DOI: 10.3354/meps09750
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs in prey quality and quantity revealed through the behavioral compensation of breeding seabirds

Abstract: Many productive ocean ecosystems are also highly variable, resulting in complex trophic interactions. We analyzed interannual patterns in the diet of a seabird, the common murre Uria aalge, in a region of high oceanographic productivity, the northern California Current, to investigate how these top predators adjust their chick provisioning to cope with environmental variability. Murres relied chiefly on Pacific herring Clupea harengus pallasi and surf smelt Hypomesus pretiosus to provision chicks, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…This may result in adjustments to their daily delivery rate when prey becomes more or less available (Welham and Beauchamp ); a response observed in many seabird species (e.g., Hamer and Hill ; Schrimpf et al. ; Kidawa et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in adjustments to their daily delivery rate when prey becomes more or less available (Welham and Beauchamp ); a response observed in many seabird species (e.g., Hamer and Hill ; Schrimpf et al. ; Kidawa et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In animals with parental care, adults act as an interface between foraging conditions and their young and must balance their own energy intake while still providing for their offspring. This may result in adjustments to their daily delivery rate when prey becomes more or less available (Welham and Beauchamp 1997); a response observed in many seabird species (e.g., Hamer and Hill 1993;Schrimpf et al 2012;Kidawa et al 2015). Experimental work on Teuri indicated that reduced meal frequency negatively affects chick body condition (Takenaka et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although nestling and adult diets may not be identical they normally encompass a similar range of prey organisms, and individual specializations tend to be reflected in both adult and offspring diets , Provencher et al 2013. A key result from numerous seabird dietary studies is that seabird productivity is associated with one or a few key species, and that when those key species become less available the diet becomes more diversified (Hedd et al 2006, Schrimpf et al 2012, Hatch 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research describing harbor seal (Phoca vitulina) predation on juvenile fish provides further evidence of size-selective predation (Tollit et al 1997, Allegue 2017, Thomas et al 2017. Measures of central tendency were summarized for preferred prey size in harbor seals (Tollit et al 1997, Lance et al 2012, Thomas et al 2017, fish predators (Duffy and Beauchamp 2008, Emmett and Krutzikowsky 2008, Beauchamp and Duffy 2011, and avian predators (Collis et al 2002, Schrimpf et al 2012, Tucker et al 2016. Measures of central tendency were summarized for preferred prey size in harbor seals (Tollit et al 1997, Lance et al 2012, Thomas et al 2017, fish predators (Duffy and Beauchamp 2008, Emmett and Krutzikowsky 2008, Beauchamp and Duffy 2011, and avian predators (Collis et al 2002, Schrimpf et al 2012, Tucker et al 2016.…”
Section: Comparing Predation Vulnerability and Release Sizementioning
confidence: 99%